Extended Abstracts of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411763.3451793
|View full text |Cite
|
Sign up to set email alerts
|

The promise and peril of parallel chat in video meetings for work

Abstract: We report the opportunities and challenges of parallel chat in workrelated video meetings, drawing on a study of Microsoft employees' remote meeting experiences during the COVID-19 pandemic.We find that parallel chat allows groups to communicate flexibly without interrupting the main conversation, coordinate action around shared resources, and also improves inclusivity. On the other hand, parallel chat can also be distracting, overwhelming, and cause information asymmetries.Further, we find that whether an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Although Sarkar et al (2021) found parallel chatting in video calls distracting and overwhelming for some users, they also identified valuable benefits from it that resonate with our participants' responses. More research needs to be done on how to integrate discreet side communication in VR.…”
Section: Meeting Productivitysupporting
confidence: 56%
“…Although Sarkar et al (2021) found parallel chatting in video calls distracting and overwhelming for some users, they also identified valuable benefits from it that resonate with our participants' responses. More research needs to be done on how to integrate discreet side communication in VR.…”
Section: Meeting Productivitysupporting
confidence: 56%
“…Although the COVID-19 pandemic has increased the visibility of WFH practices, with a recent wave of associated publications, the focus is on productivity Sarkar et al, 2021), and essentially examines remote meetings rather than socializing remotely. Past work (Stray et al, 2019) has shown that team tools such as Slack may provide opportunities for social talk alongside task-based information exchange in remote teams.…”
Section: Technologies Supporting Social Talk In the Workplacementioning
confidence: 99%
“…Past work (Stray et al, 2019) has shown that team tools such as Slack may provide opportunities for social talk alongside task-based information exchange in remote teams. In addition to teams leveraging features such as parallel chat in VC to engage in social conversations (Sarkar et al, 2021), communication however often remains problem-focused in both remote and in-person workplace environments (Calefato et al, 2020;Stray et al, 2019). With increased communication on tools such as Microsoft Teams during the pandemic (Spataro, 2020), understanding ecosystems that support social conversations become evermore important, as the frequency of communication has increased, and will likely continue, as remote work becomes more embedded in work practices.…”
Section: Technologies Supporting Social Talk In the Workplacementioning
confidence: 99%
“…Sarkar et. al [43] looked closely at the parallel chat feature within Microsoft Teams. They saw that parallel chat is helpful for participation without interrupting the primary conversation, is useful for coordinating actions (for example, via sharing links), and promoted social connection despite the online settings.…”
Section: Online Meetingsmentioning
confidence: 99%